2006
DOI: 10.1007/s00125-006-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic activation increases glycogen synthesis in L6 skeletal muscle cells through a signalling pathway independent of cyclic AMP

Abstract: Aims/hypothesis In skeletal muscle, the storage of glycogen by insulin is regulated by glycogen synthase, which is regulated by glycogen synthase kinase 3 (GSK3). Here we examined whether adrenergic receptor activation, which can increase glucose uptake, regulates glycogen synthesis in L6 skeletal muscle cells. Methods We used L6 cells and measured glycogen synthesis (as incorporation of D-[U-14 C]glucose into glycogen) and GSK3 phosphorylation following adrenergic activation. Results Insulin (negative logarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
(80 reference statements)
0
30
0
Order By: Relevance
“…To further complicate skeletal muscle ␤ 2 -adrenoceptor signaling, the G␤␥ dimer has been found to initiate intracellular signaling pathways independent of the G␣ subunit (471). Specifically, G␤␥ activates the phosphoinositol 3-kinase (PI3K)-AKT signaling pathway (Fig.…”
Section: B G Protein Coupling In Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…To further complicate skeletal muscle ␤ 2 -adrenoceptor signaling, the G␤␥ dimer has been found to initiate intracellular signaling pathways independent of the G␣ subunit (471). Specifically, G␤␥ activates the phosphoinositol 3-kinase (PI3K)-AKT signaling pathway (Fig.…”
Section: B G Protein Coupling In Skeletal Musclementioning
confidence: 99%
“…Specifically, G␤␥ activates the phosphoinositol 3-kinase (PI3K)-AKT signaling pathway (Fig. 2) (263,471). PI3K is thought to phosphorylate the membrane phospholipid phosphatidylinositol-4,5-bisphosphate (PIP 2 ), generating phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ), and creating two lipid-binding sites on the cell membrane for the serine/threonine kinase AKT (also referred to as protein kinase B) and 3Ј-phosphoinositide-dependent protein kinase 1 (PDK).…”
Section: B G Protein Coupling In Skeletal Musclementioning
confidence: 99%
“…Mechanisms that have been proposed to explain adrenergically mediated glucose uptake include stimulation of the transcription and translation of proteins, non-carrier mediated and unspecific effects, and translocation or activation of GLUTs (10,19,20), emphasizing the lack of a unifying concept for the mechanisms involved. Previously, we showed that b-adrenoceptors profoundly affect glucose uptake by an AMPK-independent pathway (3) that is not secondary to the lowering of ATP levels or energy deficiency, inasmuch as activation also increases glycogen formation in L6 skeletal muscle cells (4,21). Based on these studies and others (22), we have examined the mechanism used by b-adrenoceptors to increase glucose uptake in skeletal muscle and whether activation of this pathway could improve the condition of individuals with type 2 diabetes.…”
mentioning
confidence: 99%
“…In skeletal muscle, signaling through the β 2 -AR occurs primarily via coupling with the G protein Gα s , though there are reports describing signaling events involving Gα i and, more recently, Gβγ [58,59]. β 2 -AR coupling to Gα s activates adenylyl cyclase production of cyclic-AMP (cAMP) which in turn activates downstream signaling through protein kinase A (PKA) [60].…”
Section: β-Adrenergic Receptor Signalingmentioning
confidence: 99%